PRS5, the Fifth Member of the Phosphoribosyl Pyrophosphate Synthetase Gene Family in Saccharomyces cerevisiae, Is Essential for Cell Viability in the Absence of either PRS1 or PRS3 - Hernando, Yolanda (American Society for Microbiology, 1998)
In Saccharomyces cerevisiae, an open reading frame, YOL061w, encodes a polypeptide with sequence similarity to the four known 5-phosphoribosyl-1(α)-pyrophosphate synthetase (PRS) genes since it contains a divalent cation binding site and a phosphoribosyl pyrophosphate binding site. We regard YOL061w as the fifth member of the PRS gene family, PRS5. Loss of Prs5p has a significant impact on PRS enzyme activity, causing it to be reduced by 84%. On the other hand, Δprs5 strains are not affected in growth or in the size of their nucleotide pools. However, simultaneous deletion of PRS1 and PRS5 or PRS3 and PRS5 rendered the strains inviable, which implies that PRS5 plays an important role in the maintenance of PRS function in S. cerevisiae.